Analisis Yuridis Actio Pauliana terhadap Penyitaan Boedel Pailit (Studi Putusan Mahkamah Agung Nomor 560 K/Pdt.Sus-Pailit/2021) - Havizah Maha; Syaddan Dintara Lubis (LPPM Universitas Ekasakti Padang, 2023)
The Bankruptcy Law regulates actio pauliana. Bankruptcy cases in actio pauliana lawsuits are regulated in Article 41-42 of Law No. 37 of 2004 concerning Bankruptcy and PKPU and actio pauliana lawsuits in bankruptcy are the absolute authority of the curator, especially bankrupt debtors in a state of insolvency. However, the Supreme Court through Decision Number 560 K/Pdt.Sus-Pailit/2021 canceled the Actio Pauliana decision in the Medan Commercial Court decision Number 3/Pdt.Sus-lain other/PN Niaga Mdn and Case Register Number 1/Pdt.Sus-Actio Pauliana /2018/PN.Niaga.Mdn Jo Number 16/Pdt.Sus-PKPU/2017/PN Niaga Medan The Commercial Court has granted the actio Pauliana submitted by the Curator. The purpose of this writing is to analyze why the Supreme Court canceled the actio pauliana which had been granted by the Medan Commercial Court. The method used is normative juridical with a statutory approach and court decisions. The results of the study show that the actio pauliana case does not fulfill the elements of